A study of crowd-shipping as a last-mile delivery option in Singapore: business-to-consumer perspective - Lim, Sean Jun Hao (Nanyang Technological University, 2023)
Last-mile logistics, commonly referred to as last-mile delivery, represents the final phase in the supply chain, where products are transported from warehouses or stores to their ultimate destinations, which can be residences or businesses. In recent years, technological advancements and an increased focus on sustainability have given rise to an innovative model called crowd-shipping. While this model is celebrated for its advantages, it also carries certain drawbacks. In the urban setting of Singapore, last-mile logistics presents a particularly costly challenge, necessitating an evaluation of the feasibility of adopting crowd-shipping as a last-mile delivery option. The report aims to explore the feasibility of adopting crowd-shipping as a last-mile delivery option for businesses by understanding and characterizing the factors affecting the businesses' last-mile strategy before looking into crowd-shipping as a suitable model. The report uses a qualitative method of data collection where semi-structured interviews were conducted with two business owners to gain a deeper understanding of their considerations for their respective last-mile strategies. An analysis of the interview results was carried out using inductive thematic analysis, which revealed common factors influencing a business's choice in its last-mile operations. These identified factors include consumer behavior within the industry, the volume of a business's sales, and the scale at which the business operates. The findings will then be cross-examined with existing literature to help in identifying a common trend or key factors. These insights will make a valuable contribution to the research on the adoption of the crowd-shipping model in Singapore for last-mile delivery.